Day care management of grade I and II bleeding hemorrhoids - Trivedi, Bhushan; Wilkinson, T. R. V.; Akhtar, Murtaza (International Surgery Journal, 2019)
Background: Hemorrhoids occur in up to 80% of the population, involving any age and affecting males and females equally1 First and second-degree hemorrhoids can be treated conveniently on an out-patient basis by sclerotherapy and rubber band ligation 2. This study aims at comparing outcomes of these modalities for the treatment of grade I and II bleeding hemorrhoids. Methods: In NKP Salve institute of Medical Sciences and Research Centre hospital based nonrandomized comparative study, patients clinically diagnosed as Grade I and II bleeding hemorrhoids were included. Subjects were divided in into two groups i.e Barron’s banding and Injection of Sclerosant. The post procedural complications for the first 24 hrs were recorded, follow up was taken at regular intervals and any complications were recorded. Results: A total of 50 patients were enrolled with mean age 42.01 years and a male preponderance, with 31 males and 19 females. Barron’s banding was carried out in 25 subjects and the 25 subjects were subjected to Injection of sclerosant the mean duration taken for Injection of sclerosant was 13.6 min and in Barron’s banding 16.4 min. In the first 24hrs post procedural bleeding was observed in 40% subjects in the Barron’s banding group and 52% in the injection of sclerosant group. For post procedural pain the mean VAS score in the Barron’s group was 1.84 and 0.96 in injection of sclerosant group, follow up at 3rd month showed 16% recurrence of bleeding and 32% in injection of sclerosant group. Conclusions: Injection of sclerosant is better than Barron’s banding procedure in terms of post procedural pain.